Psychometric Properties and Measurement Invariance of the Brief Symptom Inventory-18 Among Chinese Insurance Employees - Li, Mingshu; Wang, Meng-Cheng; Shou, Yiyun; Zhong, Chuxian; Ren, Fen; Zhang, Xintong; Yang, Wendeng (Frontiers in Psychology, 2018)
This study aimed to examine the psychometric properties and factorial invariance of the Brief Symptom Inventory-18 (BSI-18). Confirmatory factor analyses (CFAs) were performed to verify the BSI-18’s factor structure in a large sample of Chinese insurance professionals (N = 2363, 62.7% women; age range = 19–70). Multigroup CFA were performed to test the measurement invariance of the model with the best fit across genders. In addition, structural equation modeling was conducted to test the correlations between the BSI-18 and two covariates – social support perception and grit trait. Results indicated that the bi-factor model best fit the data and was also equivalent across genders. The BSI-18’s general factor, and somatization and depression dimensions were significantly related to social support perception and grit trait, whereas the anxiety dimension was not. Overall, our findings suggested that the BSI-18’s can be a promising tool in assessing general psychological distress in Chinese employees.